2021
DOI: 10.3389/fimmu.2021.750386
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Mouse Monoclonal Antibodies That Neutralize SARS-CoV-2 and Its Variants of Concern Alpha, Beta, Gamma and Delta by Binding Conformational Epitopes of Glycosylated RBD With High Potency

Abstract: Antibodies targeting Receptor Binding Domain (RBD) of SARS-CoV-2 have been suggested to account for the majority of neutralizing activity in COVID-19 convalescent sera and several neutralizing antibodies (nAbs) have been isolated, characterized and proposed as emergency therapeutics in the form of monoclonal antibodies (mAbs). However, SARS-CoV-2 variants are rapidly spreading worldwide from the sites of initial identification. The variants of concern (VOC) B.1.1.7 (Alpha), B.1.351 (Beta), P.1 (Gamma) and B.1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…For example, antibodies generated by the Alpha, Beta, Gamma, and Delta variants are not efficient against Omicron, even though they share some mutations [56]. In contrast, it has been shown that monoclonal antibodies made from a recombinant RBD (Wuhan sequence) neutralized major variants [57]. However, in our case a full C-terminal domain of the S1 protein along the RBD domain was introduced and might affect the production of new neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 88%
“…For example, antibodies generated by the Alpha, Beta, Gamma, and Delta variants are not efficient against Omicron, even though they share some mutations [56]. In contrast, it has been shown that monoclonal antibodies made from a recombinant RBD (Wuhan sequence) neutralized major variants [57]. However, in our case a full C-terminal domain of the S1 protein along the RBD domain was introduced and might affect the production of new neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 88%
“…Expression plasmids encoding wild type and variants of concern (VoC) Spike ORFs used in the pseudovirus neutralization assay were previously described ( 45 , 46 ) and are depicted in Supplementary Figure 1B . Briefly, plasmid pSpike-C3 encodes the wild type (Wuhan-Hu-1) codon optimized SARS-CoV-2 delta21 Spike protein open reading frame (ORF) ( 40 ); plasmids pSpike-UKC3, pSpike-SAC3 and pSpike-BRC3 encode the delta21 codon optimized B.1.1.7 (Alpha), B.1.351 (Beta) and P.1 (Gamma) Spike ORFs, respectively, while plasmid pSpike-INC3 encodes the B.1.617.2 (Delta) Spike ORF with a 19 aa deletion in the cytoplasmic tail ( 45 , 46 ).…”
Section: Methodsmentioning
confidence: 99%
“…Integrase competent Lentiviral Vector expressing Luciferase (LV-Luc) and pseudotyped either with Indiana or Cocal VSV.G were tittered in VERO E6 cells and used in the neutralization assays 66 , 67 . Briefly, 5-fold serial dilutions starting from 1/100 of heat inactivated sera from immunized monkeys were incubated with 200.000 relative luminescence units (RLU) of LV-Luc/VSV.G In or LV-Luc/VSV.G Co in 96 deep well plate plates (Resnova, Genzano di Roma, Italy) at 37 °C for 30 minutes at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Results are expressed as inhibitory dilution (ID) 50 corresponding to the serum dilution giving 50% inhibition of infection (neutralization) compared to the virus-only control wells after background subtraction in cell control wells. ID50 was calculated with a linear interpolation method 66 , 67 .…”
Section: Methodsmentioning
confidence: 99%